1989
DOI: 10.1128/jcm.27.9.1979-1982.1989
|View full text |Cite
|
Sign up to set email alerts
|

Indirect enzyme-linked immunosorbent assay for zygomycosis

Abstract: A 2-h indirect enzyme-linked immunosorbent assay (ELISA) using homogenate antigens of Rhizopus arrhizus and Rhizomucor pusillus was developed and compared with the existing immunodiffusion (ID) test for zygomycosis, using homogenate antigens of R. arrhizus. Utilizing 1:400 as a minimally positive ELISA titer, 33 of 43 proven cases of zygomycosis were diagnosed. The sensitivity of the ELISA was 81%. The ID test, in contrast, detected only 21 cases and demonstrated a sensitivity' of 66%. The specificity of the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…The experimental use of serologies to detect invasive zygomycosis has been attempted in several laboratories (154,198,220,230,275,365,417,429,517,522). Although several serologic modalities have been tested, the enzymelinked immunosorbent assays (ELISA) seem to have the best sensitivity and specificity for detecting antibodies produced during invasive zygomycosis (230,365). These serologically based tests have demonstrated that the zygomycetes share several antigenic determinants with one another.…”
Section: Serologic Diagnosis Of Infections With the Zygomycetesmentioning
confidence: 99%
See 4 more Smart Citations
“…The experimental use of serologies to detect invasive zygomycosis has been attempted in several laboratories (154,198,220,230,275,365,417,429,517,522). Although several serologic modalities have been tested, the enzymelinked immunosorbent assays (ELISA) seem to have the best sensitivity and specificity for detecting antibodies produced during invasive zygomycosis (230,365). These serologically based tests have demonstrated that the zygomycetes share several antigenic determinants with one another.…”
Section: Serologic Diagnosis Of Infections With the Zygomycetesmentioning
confidence: 99%
“…These serologically based tests have demonstrated that the zygomycetes share several antigenic determinants with one another. This antigenic sharing makes it impossible for the various species and even genera to be reliably distinguished from one another (198,230,365). In addition to detecting antibody production due to invasive disease, double-diffusion and ELISA techniques have been used to detect antibodies produced as a result of allergic alveolitis (404).…”
Section: Serologic Diagnosis Of Infections With the Zygomycetesmentioning
confidence: 99%
See 3 more Smart Citations